Toothache experiences - Elyda Akhya Afida Misrohmasari; Dimas Wicaksono; Hestieyonini Hadnyanawati; Berlian Prihatiningrum (Universidade Estadual de Campinas, 2022)
Aim: To describe the pattern of toothache experience in a cohort of children aged 2-5 over 21 years and to find the relationship between previous toothache experience and later reports of toothache to get finding on the most critical period of toothache as a problem in life. Methods: This is a secondary data analysis from Indonesia Family Life Survey (IFLS). A total of 1,927 children from IFLS-1 with complete data were included as baseline participants. They were followed up four times within 21 years (age 6-9y, age 9-12y, age 16-19y, age 23- 26y). Toothache was based on the question of self-reported toothache experience during the last four weeks. After 21 years, a total of 1,098 individuals could be traced and completed every cohort of the survey. Toothache experiences were reported for frequencies in every cohort and accumulative experiences over 21 years. Logistic regression tests were performed to analyze the association of previous toothache experience and later toothache experience. Results: Almost 40% of the respondents reported toothache at least once in their life. The age of 6-9 years is the period when a high percentage of children had teeth-related pain. The experience of toothache at this period was significantly related to every period of age in life. Conclusions: The period of early mixed dentition is important. Oral health status in this period is associated with future oral health. A comprehensive dental health prevention program targeting this population is essential to increase the quality of life.